Taxonomy of Cooperation and Reciprocity: Beyond Interdisciplinary Social Science Imperialism - Elias L. Khalil (20518877) (2025)
The literature on cooperation acknowledges different forms of cooperation and their corresponding forms of reciprocity. This paper goes further and shows that most of these different forms are indeed distinct types; hence, the terms “cooperation” and “reciprocity” are portmanteau. This paper proposes a taxonomy of ten types: i) quid pro quo; ii) intertemporal allocation; iii) altruism; iv) formal obligations (justice); v) informal obligations (repayment of favors); vi) gifts; vii) allegiance; viii) hegemony; ix) grants; and x) philanthropy. Nonetheless, “beneficence”, defined as the promotion of the good, is common to all ten types. The promotion of the good entails actions that are free from i) opportunism and deception; ii) self-aggrandizement; and iii) malevolence (envy, schadenfreude, etc.). One payoff of the proposed ten-type taxonomy of cooperation/reciprocity is the delineation of five disciplines: anthropology, economics, political science, sociology, and psychology. Each discipline is suitable for the study of one or two types of cooperation/reciprocity. This raises a question: how does each discipline conceive of the other types appropriate for adjacent disciplines? This paper finds that each discipline effectively sculptures the other types after its own preconceived mode of conception (toolkit)—amounting to “interdisciplinary social science imperialism.” The proposed ten-type taxonomy promises a transdisciplinary platform that is impartial, i.e., able to help researchers avoid interdisciplinary imperialism. This payoff shows the possibility of unifying the social sciences without interdisciplinary imperialism, i.e., reducing all types of cooperation/reciprocity to one’s favored preconceived toolkit. Other Information Published in: Integrative Psychological and Behavioral Science License: https://creativecommons.org/licenses/by/4.0 See article on publisher's website: http://dx.doi.org/10.1007/s15010-020-01480-x